Glial Cells in Glaucoma: Friends, Foes, and Potential Therapeutic Targets - García-Bermúdez, Mariana Y.; Freude, Kristine K.; Mouhammad, Zaynab A.; van Wijngaarden, Peter; Martin, Keith K.; Kolko, Miriam (Frontiers in Neurology, 2021)
Glaucoma is the second leading cause of blindness worldwide, affecting 80 million people by 2020 (1, 2). The condition is characterized by a progressive loss of retinal ganglion cells (RGCs) and their axons accompanied by visual field loss. The underlying pathophysiology of glaucoma remains elusive. Glaucoma is recognized as a multifactorial disease, and lowering intraocular pressure (IOP) is the only treatment that has been shown to slow the progression of the condition. However, a significant number of glaucoma patients continue to go blind despite intraocular pressure-lowering treatment (2). Thus, the need for alternative treatment strategies is indisputable. Accumulating evidence suggests that glial cells play a significant role in supporting RGC function and that glial dysfunction may contribute to optic nerve disease. Here, we review recent advances in understanding the role of glial cells in the pathophysiology of glaucoma. A particular focus is on the dynamic and essential interactions between glial cells and RGCs and potential therapeutic approaches to glaucoma by targeting glial cells.